HATCHING SUCCESS OF Clarias gariepinus EGG USING DIFFERENT INCUBATING SUBSTRATES AND VARYING EGG AREA DENSITY - SOLOMON, S.G; OKOMODA, V.T; ATAGUBA, G.A; IKWUTA, Q. O. (Nigerian Journal of Fisheries, 2015)
This study evaluated the efficiency of different substrates and best egg area density for hatching Clarias gariepinus egg. The different substrates used were Polyvinyl chloride (PVC) frame with fine mesh (1 mm x 1mm) net, fine mesh net, sack thread and the control was without a substrate. Result obtained shows that eggs hatched on PVC frame with fine mesh net and ordinary fine mesh net had higher hatchability (79.40% and 77.55% respectively) compared to eggs hatched on sack (64.75%) and the control bowl without a substrate (20.70%). However, screening efficiency of un-hatched eggs from the hatched eggs were better using PVC frame with fine mesh net compared to other forms of substrate used. Based on the efficacy of PVC frame with fine mesh net substrate, this substrate was then used for the next study which was designed to determine the best area density for optimum hatching; increasing egg-mesh ratio (estimated in gcm-2 i.e. mass of egg to the mesh area) namely, 0.58, 1.16, 1.74, 2.31, 2.85, 3.47,4.05, 4.64 and 5.52 was used for this study.The result revealed that beyond 4.05 area density, hatchability was significantly reduced (below 50%). Hence, for higher hatching success of African catfi